NOISE RISK ASSESSMENT AT AIR SEPARATION PLANT PT. X SURABAYA (NITROGEN, OXYGEN, AND ARGON PLANT) - Diniari, Hanif Rizqi; Eka Prasetya, Tofan Agung; Nawawiwetu, Erwin Dyah; Tualeka, Abdul Rohim (Faculty of Vocational Studies, Universitas Airlangga, 2017)
Background: Noise was one of the dangerous factors at a workplace which causes various effects on workers. Purpose: The purpose of this research was to described the activity stages, identified the noise danger, and assessed the risk and its level at Air Separation Plant of PT. X. Method: This research was a descriptive research with a cross sectional approach. The object of the research was the noise danger potential and the noise risk level assessment at Air Separation Plant of PT. X. Result: The result of this research showed that there were 12 identified noise danger points. These results consisted of 5 (42 %) noise risks with low category, 2 (16 %) with middle category, and another 5 (42 %) with high category. The highest noise intensity measurement result was found on Recycle Nitrogen Compressor (RNC) machine, which was 116,5 dBA. Conclusion: Based on this data, it can be concluded that there were 12 identified noise danger points and the highest noise intensity measurement result was found on Recycle Nitrogen Compressor (RNC) machine, which was 116,5 dBA. It is suggested for the related company to execute controls mostly in diminishing the noise sources.